The Elastıc Bıte-Block - Nejat Erverdi; Gökhan Özkan (Galenos Yayinevi, 1994)
The Elastic Bite Block appliance was developed with the idea of getting the advantage of increased functional activity due to the interocclusal soft material. Appliance was designed to achieve the compound effect of the extraoal force together with the functional appliance. Some advantages of this clinically effective design are its simplicity in construction and possibility of correcting mild crowdings together with the functional improvement. In this article the appliance was introduced and one of our case was presented.